Analisis Perbandingan Model Pendeteksi Financial Distress Pada Perusahaan Sektor Aneka Industri: - - Tesa Rahmita; Ferdawati Ferdawati; Reni Endang Sulastri (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research aims to determine the financial condition of various industrial sector companies listed on the Indonesia Stock Exchange for the period 2015-2019, using a purposive sampling method with a total sample of 13 companies. The type of data used is secondary data obtained from the company's financial statements. This study uses 3 models of financial distress analysis, namely the Springate, Grover and CA-Score models. The results of this study indicate that the Springate model predicts that twelve companies are in a state of distress for five consecutive years and one company is in a state that changes from distress to non-distress. The Grover model predicts that four companies are in a state of distress, four companies are in a non-distress condition and five companies are in a fluctuating condition for five consecutive years. The CA-Score model predicts that there are five companies that are in a distress condition, five companies are in a non-distress condition and three companies that are in a fluctuating condition for five consecutive years.